MONKEY POX (M-Pox/MPXV): Epidemiology, transmission, clinical findings, treatment and herbal treatment - Mustafa Sevindik; Memet Yazar
There is a serious increase in the number of viral diseases today. Monkeypox virus (M-Pox/MPXV) is defined as a viral infection caused by a virus called Orthopoxvirus in the Poxviridae family. It is frequently found in the tropical rainforests of West and Central Africa. However, it has spread to other countries over time. In this study, the Monkeypox virus, which has recently caused a significant number of deaths, was examined in detail. Based on the literature data, the health problems, symptoms, and treatment approaches caused by the disease were discussed. In addition, natural products that can be effective using traditional treatment methods were compiled. As a result, this study can be a source of treatment approaches for the Monkeypox virus